2020
DOI: 10.1038/s42003-020-01389-z
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing protein dynamics from fluorescence intensity traces using unsupervised deep learning network

Abstract: We propose an unsupervised deep learning network to analyze the dynamics of membrane proteins from the fluorescence intensity traces. This system was trained in an unsupervised manner with the raw experimental time traces and synthesized ones, so neither predefined state number nor pre-labelling were required. With the bidirectional Long Short-Term Memory (biLSTM) networks as the hidden layers, both the past and future context can be used fully to improve the prediction results and can even extract information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Classification time for a given trace was on a sub-millisecond timescale, opening the door to real-time analysis of oligomer distributions during highthroughput experiments. In comparison to the literature study (Xu et al, 2019;Yuan et al, 2020), the accuracy of our deep learning methods is similar, but we have demonstrated that our approach is applicable to even larger oligomers. Furthermore, our approach is quite flexible since photobleaching and imaging noise are physical phenomena well understood, making simulation a valid way to train a model and obtain training parameters before applying them to experimental photobleaching traces.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Classification time for a given trace was on a sub-millisecond timescale, opening the door to real-time analysis of oligomer distributions during highthroughput experiments. In comparison to the literature study (Xu et al, 2019;Yuan et al, 2020), the accuracy of our deep learning methods is similar, but we have demonstrated that our approach is applicable to even larger oligomers. Furthermore, our approach is quite flexible since photobleaching and imaging noise are physical phenomena well understood, making simulation a valid way to train a model and obtain training parameters before applying them to experimental photobleaching traces.…”
Section: Discussionsupporting
confidence: 80%
“…We note that the well-known Chung-Kennedy algorithm ( Chung and Kennedy, 1991 ) and the Hidden Markov model (HMM) analysis ( Messina et al, 2006 ) are computationally expensive. The application of machine learning approaches in single-molecule analysis has gained considerable interest recently ( Meng et al, 2022 ; Xu et al, 2019 ; Yuan et al, 2020 ; Thomsen et al, 2020 ; White et al, 2020 ; Li et al, 2020 ). A deep learning algorithm named DeepFRET has been demonstrated to reach classification accuracy on ground truth data by over 95%, not only outperforming human operators but also reducing the computation time by two orders of magnitude ( Thomsen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(b) The training and performances of DGN on both photobleaching event counting and dynamic finding with fluorescence intensity traces. 100 Copyright © 2020, The Author(s). 104 Copyright © 2020, The Author(s)…”
Section: Deep-learning-assisted Single Molecule Fluorescence Intensit...mentioning
confidence: 99%
“…Copyright © 2019, American Chemical Society. (b) The training and performances of DGN on both photobleaching event counting and dynamic finding with fluorescence intensity traces 100. Copyright © 2020, The Author(s).…”
mentioning
confidence: 99%